Implications of Concurrent IDH1 and IDH2 Mutations on Survival in Glioma—A Case Report and Systematic Review - Alexander Yuile; Laveniya Satgunaseelan; Joe Wei; Marina Kastelan; Michael F. Back; Maggie Lee; Heng Wei; Michael E. Buckland; Adrian Lee; Helen R. Wheeler (Current Issues in Molecular Biology, 2022)
Both IDH1 (isocitrate dehydrogenase 1) and IDH2 (isocitrate dehydrogenase 2) mutations play a vital role in the development of gliomas through disruption of normal cellular metabolic processes. Here we describe a case of a patient with an IDH-mutant astrocytoma, in which both IDH1 and IDH2 mutations were detected within the same tumour. The patient remains disease-free, nine and a half years after her initial diagnosis. Interrogation of cancer genomic databases and a systematic review was undertaken, demonstrating the rarity of the co-occurrence of IDH1 and IDH2 mutations in a variety of cancer types, and in glioma specifically. Due to the favourable outcome observed in this patient, the potential effect of concurrent IDH1 and IDH2 mutations on survival was also investigated.